2022
DOI: 10.3389/fpsyg.2022.1061631
|View full text |Cite
|
Sign up to set email alerts
|

Associations between parental mediation and adolescents' internet addiction: The role of parent–child relationship and adolescents' grades

Abstract: IntroductionFamily factors, such as parental mediation on Internet use and parent-child relationships, have been shown to play a crucial role in preventing adolescents' internet addiction. Previous studies have shown a change in characteristics of online risk during adolescents' development. However, it is still of great interest whether such differences applied in the relationships among parent-child relationships, different types of parental mediation and adolescents' internet addiction level. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…In contrast, authoritarian and permissive parenting styles result in aggressive and negative behaviors in children (68). On the other hand, several studies have found that active mediation has been linked to a decrease in adolescents' internet addiction (13). Additionally, one recent study showed that restrictive mediation decreased contact with new people by increasing adolescents' risk perception of this activity.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, authoritarian and permissive parenting styles result in aggressive and negative behaviors in children (68). On the other hand, several studies have found that active mediation has been linked to a decrease in adolescents' internet addiction (13). Additionally, one recent study showed that restrictive mediation decreased contact with new people by increasing adolescents' risk perception of this activity.…”
Section: Discussionmentioning
confidence: 99%
“…The data collected from 841 mothers’ reports in this study confirmed the positive relationship between mindful parenting and preschoolers’ creative tendencies. A recent study of adolescents aged 12–15 years and their parents discovered that the higher the parents’ degree of mindful parenting, the better the development of their children’s creativity and their level of creativity in all its dimensions [ 51 ]. Our findings support previous research, broaden the age range of existing studies, and give additional empirical evidence for shaping children’s creative tendencies.…”
Section: Discussionmentioning
confidence: 99%
“…These six categories are also organized into three information types: entertainment and lifestyle are the stress-reducing type; learning and work are the stress-producing type; and political news and social are the neutral type (meaning that reading such information does not directly reduce or produce stress). Previous studies have shown that the different types and categories of Internet content preferences have different effects on Internet addiction ( 22 , 23 ). Accordingly, the present study explored the associations of different types and categories of phone Internet contents with mobile phone dependence and depressive symptoms among Chinese university students.…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged use may produce feelings of exhaustion and loss ( 37 ), and some Internet users experience guilt or even depressive symptoms after flow experiences ( 38 ). Some studies have found that Internet content categories such as entertainment are more likely to cause Internet addiction and dependence in adolescents ( 22 ). Based on this, we propose the following hypothesis:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation